Nonlinear pulse compression of a thin-disk amplifier and contrast enhancement via nonlinear ellipse rotation - Pfaff, Yanik; Forster, Carola; Barbiero, Gaia; Rampp, Michael; Klingebiel, Sandro; Brons, Jonathan; Teisset, Catherine Y.; Wang, Haochuan; Jung, Robert; Jaksic, Jasna; Woldegeorgis, Abel H.; Saraceno, Clara J.; et al. (Optics Express, 2022)
We demonstrate pulse compressibility from 840 fs to 38 fs of 10 mJ pulses from a thin-disk amplifier at a repetition rate of 3 kHz after nonlinear broadening in a multipass cell. In addition, the temporal-intensity contrast is enhanced via nonlinear ellipse rotation of more than a factor 50 with an optical efficiency of 56%. We believe this is the first published experimental combination of multipass cell-based nonlinear compression and nonlinear ellipse rotation-based contrast enhancement preserving both pulse compressibility and beam quality.
CRIS-Team Scopus Importer:2022-04-01